Socialization of Personality in the Context and Foreign Scientific and Pedagogical Research - Avramenko, Oksana (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
In article the essence of the concept of socialization, examines the state of development of the problem of socialization of the individual in the domestic and foreign science, defined the scientific achievements of scientists. Аnalysis interpretations of the essence of socialization that exist in the concepts and theories of socialization (sociological, cultural, social, psychological, pedagogical concept) suggests that socialization is essential attributes: the process of influence social environment on the individual, the transmission of cultural experiences, adaptation to social conditions targeted forming collectivist qualities. Socialization provides entry rights in social and community groups, comfortable coexistence in them, the socialization of its activities, lifestyles and opinions, to form individual members of certain communities and social groups, social strata. The new socio-cultural situation and the requirements of society to provide for the individual is not just a passive adaptation to the individual requirements of society and the creation of favorable conditions for the formation of social competence of pupils. So, kids should practice when entering the social environment, to cultivate mobility, flexibility of behavior, adaptive mechanisms. Mastering the science of life - a basic need of the child, which he strives to meet, and that requires skills from him not only to survive in the fast-moving environments, and to live in full force, to realize their potential, to reach agreement with the environment, to find their place in the controversial commensurate world.